1999
DOI: 10.1161/01.cir.100.suppl_2.ii-322
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nitric Oxide-Mediated Vascular Relaxation in Radial Artery Compared With Internal Mammary Artery or Saphenous Vein

Abstract: Background-The superior long-term patency of internal mammary artery coronary bypass grafts compared with venous grafts has been attributed in part to increased endothelium-derived nitric oxide (⅐NO) production. Interest in the radial artery as an alternative bypass conduit has recently been revived; however, its biological characteristics remain incompletely defined. The purpose of this study was to compare the ⅐NO-mediated vasomotor properties of the radial artery to those of the internal mammary artery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 26 publications
5
52
1
2
Order By: Relevance
“…27 Furthermore, in a previous in vitro study, endotheliumdependent dilation was intact in segments of radial artery (which is adjacent to the brachial artery) obtained from patients with advanced coronary artery disease. 28 The present study may help clarify these apparent discrepancies because our data suggest that the observed reductions in hyperemiainduced FMD% in individuals with various CRFs are attributable largely to a reduction in the stimulus for dilation during hyperemia rather than impairment in local endothelial function in the brachial artery.…”
Section: Mitchell Et Al Shear Stress and Endothelial Functionmentioning
confidence: 68%
“…27 Furthermore, in a previous in vitro study, endotheliumdependent dilation was intact in segments of radial artery (which is adjacent to the brachial artery) obtained from patients with advanced coronary artery disease. 28 The present study may help clarify these apparent discrepancies because our data suggest that the observed reductions in hyperemiainduced FMD% in individuals with various CRFs are attributable largely to a reduction in the stimulus for dilation during hyperemia rather than impairment in local endothelial function in the brachial artery.…”
Section: Mitchell Et Al Shear Stress and Endothelial Functionmentioning
confidence: 68%
“…5,6 Endothelial function is a predictor of coronary events in patients with coronary artery disease 7,8 and is associated with short-term coronary graft performance. 2 Greater endothelium-dependent relaxation occurs in vitro in precontracted IMA compared with SV after harvesting for coronary artery bypass surgery, 9,10 and although exposure of vein grafts to arterial pressure might be expected to result in further dysfunction of the endothelium, 11,12 heterogeneity in endothelium-dependent relaxation response, not related to duration of arterialization but to localized areas of intimal hyperplasia, has been reported. 13 Previous studies have shown preserved IMA graft vascular reactivity in vivo a number of years after surgery 14,15 ; however, at present there are few data describing the vascular function of the RA as an in vivo coronary conduit over the longer term.…”
Section: Editorial See P 857 Clinical Perspective On P 867mentioning
confidence: 99%
“…Other studies suggest that the endothelial function of radial artery is similar to that of the IMA (25,26). However, other investigators have reported differences in endothelium-derived NO release and hyperpolarizing factor in the IMA and radial artery (27,28 This has led researchers to look for experimental models for functional experiments in an attempt to avoid the detrimental impact of these cardiovascular risk factors on vasoreactivity. Recently, we addressed the neurogenic contractions produced in porcine radial artery using a combined histological/functional approach (4).…”
Section: +mentioning
confidence: 99%